2019
DOI: 10.12688/gatesopenres.12869.2
|View full text |Cite
|
Sign up to set email alerts
|

Deep clinical and biological phenotyping of the preterm birth and small for gestational age syndromes: The INTERBIO-21st Newborn Case-Control Study protocol

Abstract: Background: INTERBIO-21st is Phase II of the INTERGROWTH-21st Project, the population-based, research initiative involving nearly 70,000 mothers and babies worldwide coordinated by Oxford University and performed by a multidisciplinary network of more than 400 healthcare professionals and scientists from 35 institutions in 21 countries worldwide. Phase I, conducted 2008-2015, consisted of nine complementary studies designed to describe optimal human growth and neurodevelopment, based conceptually on the WHO pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Detailed information about each study site was previously published 4 , 16 . In brief, Pelotas (Brazil) is the third most populous city in the state of Rio Grande do Sul, with 350,000 inhabitants and 4,000 births per year, nearly all of which take place in the city’s four maternity hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information about each study site was previously published 4 , 16 . In brief, Pelotas (Brazil) is the third most populous city in the state of Rio Grande do Sul, with 350,000 inhabitants and 4,000 births per year, nearly all of which take place in the city’s four maternity hospitals.…”
Section: Methodsmentioning
confidence: 99%
“… Many observational studies and some randomized trials demonstrate how fetal growth can be influenced by environmental insults (for example, maternal infections) 1 and preventive interventions (for example, multiple-micronutrient supplementation) 2 that can have a long-lasting effect on health, growth, neurodevelopment and even educational attainment and income in adulthood 3 . In a cohort of pregnant women ( n = 3,598), followed-up between 2012 and 2019 at six sites worldwide 4 , we studied the associations between ultrasound-derived fetal cranial growth trajectories, measured longitudinally from <14 weeks’ gestation, against international standards 5 , 6 , and growth and neurodevelopment up to 2 years of age 7 , 8 . We identified five trajectories associated with specific neurodevelopmental, behavioral, visual and growth outcomes, independent of fetal abdominal growth, postnatal morbidity and anthropometric measures at birth and age 2.…”
mentioning
confidence: 99%
“…[2][3][4] Twelve preterm-birth phenotypes (ie, separate biological entities with specific risk factors, newborn anthropometry, and risk of neonatal morbidity and mortality) 5 have previously been identified. The present INTERBIO-21st Newborn Study 6 comprised phase 2 of the International Fetal and Newborn Growth Consortium for the 21st Century (INTERGROWTH-21st) Project, a populationbased research initiative involving almost 70 000 mothers and infants worldwide that was conducted from 2008 to 2015. In this study, we investigated whether preterm-birth phenotypes were associated with clinical, epidemiological, growth, and neurodevelopmental differences among preterm and term infants up to age 2 years.…”
mentioning
confidence: 99%
“…Despite important advances in research on the biological basis of IUGR [27][28][29] , the currently available information is complex and has not yet been translated into clinical practice. Some authors have suggested that we can improve characterization and phenotyping of pathologies, such as preterm birth 15 and IUGR 30 , based on maternal, fetal and placental clinical conditions. Accordingly, 12 preterm-birth phenotypes associated with differing neonatal outcome 17 and neurodevelopmental outcome up to 2 years of age 31 were identified recently.…”
Section: Discussionmentioning
confidence: 99%